Boron-doped nanographene light-emitting material, preparation method and application thereof

CN117903184BActive Publication Date: 2026-10-27JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410091878.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-23
Publication Date
2026-10-27
Estimated Expiration
2044-01-23

AI Technical Summary

Technical Problem

[0005]有鉴于此,为解决现有技术中硼杂纳米石墨烯发光材料的数量少、合成难度大等问题,本发明提供一类硼杂纳米石墨烯发光材料及其制备方法与应用,实现了该类材料的放大自发发射功能,为发展有机激光增益介质材料提供了体系和新方向

Benefits of technology

本发明提供的硼杂纳米石墨烯发光材料对水、氧气具有良好的稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117903184B_ABST
    Figure CN117903184B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of boron nano graphene light-emitting materials and its preparation method and application, belong to organic laser gain medium material technical field.Solve the technical problems such as few quantity of boron nano graphene light-emitting material in prior art, synthesis difficulty.The boron nano graphene light-emitting material of the present application, structural formula is as shown in formula 1-10.The boron nano graphene light-emitting material has good stability to water, oxygen, has good solubility in a variety of solvents, for example, in chloroform, toluene, tetrahydrofuran, and has excellent luminescent performance and amplified spontaneous emission properties, so that it is expected to become good performance organic laser gain medium material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organic laser gain medium technology, specifically relating to a class of boron-hybrid graphene nanoluminescent materials with amplified spontaneous emission properties, their preparation methods and applications, and particularly to the application of this class of boron-hybrid graphene nanoluminescent materials as laser gain materials. Background Technology

[0002] The carbon atoms in graphene are arranged in sp... 2 Hybrid orbitals form a two-dimensional honeycomb structure, possessing unique physical and electronic properties that have attracted widespread attention in the materials science community. Nanographene, a segmental structure of graphene, has a well-defined atomic composition and topological structure, and has become a cutting-edge interdisciplinary field in synthetic chemistry, organic electronics, and nanotechnology. Compared to graphene, nanographene possesses a definite chemical and electronic structure, thus enabling more precise realization of optical and electrical functions, and holds promise as a next-generation organic optical and electrical functional material.

[0003] Lasers are ubiquitous in our daily lives, appearing in scanners, printers, and sensors. Solid-state lasers, capable of precisely controlling the temporal, spectral, and spatial characteristics of laser light, have expanded the field of spectroscopy and provided record-breaking sensitivity and resolution. A necessary condition for laser generation is that the material possesses optical gain properties. Amplified spontaneous emission (ASE) is a good method for detecting whether a material possesses laser gain properties. Its principle is to excite an organic light-emitting material with a strip-shaped pulsed laser and collect the edge emission from the material. In the absence of an optical feedback structure, photons generated through spontaneous emission can amplify the excited emission if they interact with other light-emitting substances in the gain material. Nanographene, due to its high environmental stability and unique optical properties, holds promising applications in the field of laser gain materials. However, currently, only a few examples of nanographene exhibiting amplified spontaneous emission capabilities have been reported in the literature. The problem stems from the difficulty in controlling the electronic structure of nanographene due to its all-carbon structure, making excited-state control even more challenging. Therefore, exploring nanographene with amplified spontaneous emission capabilities holds promise for realizing a new type of organic laser gain medium material.

[0004] Introducing heteroatoms into graphene nanoparticles and utilizing the orbital interactions between heteroatoms and the π-conjugated system, as well as the spatial structure of heteroatoms, can effectively control the orbital energy levels, optical band gap, luminescence efficiency, and excited-state lifetime of graphene nanoparticles, thereby enabling high-performance and multifunctional hybrid graphene nanoparticle luminescent materials. In the periodic table, boron atoms are adjacent to carbon atoms and possess a characteristic empty p orbital. Therefore, for π-conjugated organoboron compounds, the p orbital of boron atoms generates p-π conjugation with the π-conjugated system, exhibiting strong electron deficiency, excellent charge transport properties, and luminescence capabilities. This suggests new functions and application potential in controlling supramolecular polymerization, photoinduced dissociation and fluorescence behavior, and dynamic regulation of biradicals. However, the high sensitivity of boron atoms to water and oxygen, and the instability of organoboron compounds, make the design and synthesis of boron-hybrid graphene nanoparticles difficult, and functional exploration extremely challenging, thus limiting the development of boron-hybrid graphene nanoparticle luminescent functional materials. Summary of the Invention

[0005] In view of this, in order to solve the problems of low quantity and high synthesis difficulty of boron-impregnated graphene nanomaterials in the prior art, this invention provides a class of boron-impregnated graphene nanomaterials, their preparation methods and applications, realizing the amplified spontaneous emission function of this type of material, and providing a system and new direction for the development of organic laser gain medium materials.

[0006] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows.

[0007] This invention provides a class of boron-impregnated graphene nanomaterials with one of the following structural formulas: .

[0008] The present invention also provides the application of the above-mentioned boron-hybridized graphene nanoluminescent material as an organic laser gain medium material.

[0009] Compared with the prior art, the beneficial effects of the present invention are as follows: The boron-impregnated graphene nanomaterial provided by this invention has good stability against water and oxygen.

[0010] The boron-impregnated graphene nanomaterials provided by this invention have good solubility in a variety of solvents, such as chloroform, toluene, and tetrahydrofuran.

[0011] The boron-hybrid graphene nanomaterial provided by this invention has excellent luminescence performance and amplified spontaneous emission properties, making it a promising organic laser gain medium material with excellent development prospects in the field of organic optical functional materials.

[0012] Based on the existing synthesized boron-hybrid graphene nanomaterials of this invention, it is speculated that the principle may be as follows: boron atoms and the π-conjugated system generate p-π conjugation, which promotes the effective delocalization of electrons in boron-hybrid graphene nanomaterials, forming highly overlapping LUMO and HOMO orbitals, thereby suppressing the electronic structure polarization of the excited state and bringing about a long excited state lifetime and high luminescence performance, thus realizing the amplification of spontaneous emission function and organic laser gain material. Attached Figure Description

[0013] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0014] Figure 1 High-resolution mass spectra (insets) and full mass spectra of the boron-impregnated graphene nanomaterials prepared in Examples 1, 2, 3 and 4 of this invention; Figure 2 a), b), c), and d) in the figures represent the ultraviolet-visible absorption spectra of the boron-impregnated graphene nanomaterials prepared in Examples 1, 2, 3, and 4 of this invention, respectively. Figure 3 a), b), c), and d) in the figures represent the emission spectra of the boron-impregnated graphene nanomaterials prepared in Examples 1, 2, 3, and 4 of this invention, respectively. Figure 4 The image shows the amplified spontaneous emission characteristics of the boron-doped graphene nano-luminescent material prepared in Example 1 of this invention. In this image, a) is the photoluminescence spectrum of the polystyrene-doped film (3 wt% of compound 1) under different laser powers, and the inset is a fluorescence photograph of the polystyrene-doped film; b) is the relationship between the full width at half maximum (FWHM) and emission peak intensity of the polystyrene-doped film (3 wt% of compound 1) and the laser power. Figure 5 The image shows the amplified spontaneous emission characteristics of the boron-doped graphene nanoluminescent material prepared in Example 2 of this invention. In the image, a) is the photoluminescence spectrum of the polystyrene-doped film (3wt% of compound 2) under different laser powers, and the inset is a fluorescence photograph of the polystyrene-doped film; b) is the relationship between the full width at half maximum (FWHM) and emission peak intensity of the polystyrene-doped film (3wt% of compound 2) and the laser power. Figure 6The diagram shows the amplified spontaneous emission characteristics of the boron-doped graphene nanomaterial prepared in Example 3 of this invention. A) shows the photoluminescence spectrum of the polystyrene-doped film (20 wt% of compound 3) under different laser powers; b) shows the relationship between the full width at half maximum (FWHM) and emission peak intensity of the polystyrene-doped film (20 wt% of compound 3) and the laser power; c) shows the UV-Vis absorption spectra and amplified spontaneous emission performance of polystyrene-doped films with different proportions (0 wt%, 3 wt%, 20 wt%, 50 wt% of compound 3). The inset shows the fluorescence photographs of the corresponding polystyrene-doped films. Detailed Implementation

[0015] To enable those skilled in the art to better understand the technical solutions of the present invention, the present invention will be further described in detail below with reference to embodiments.

[0016] In the following embodiments, various processes and methods not described in detail are conventional methods known in the art. Unless otherwise specified, the materials, reagents, apparatus, instruments, equipment, etc., used in the following embodiments are commercially available.

[0017] Example 1: Synthesis of Compound 1 Tricoordinated boron unit 11 (51.0 mg, 0.102 mmol), 6,13-dipinacolboryl ester-2-(tert-butyl)-9b-borona[1,8-ab]perylene (30 mg, 0.046 mmol), tetraphenylphosphine palladium (5.4 mg, 0.0047 mmol), 2-dicyclohexylphosphine-2',6'-dimethoxy-1,1'-diphenyl (3.8 mg, 0.0093 mmol), and potassium phosphate (39 mg, 0.18 mmol) were added to a dry reaction flask equipped with a condenser. After three or more vacuuming and argon purging operations, dry toluene (8 mL), deoxygenated ethanol (1 mL), and deoxygenated water (1 mL) were sequentially added. The temperature was then raised to 100°C. o The reaction proceeded for 7 hours. After the reaction was complete, the reaction mixture was added to water, and the aqueous phase was extracted three times with ethyl acetate (30 mL). The resulting ethyl acetate phase was washed once with water, and the organic phases were combined and dried over anhydrous sodium sulfate. After removing the solvent under reduced pressure, the crude product was separated by column chromatography using 200-300 mesh silica gel as the stationary phase and dichloromethane:petroleum ether = 1:8 (volume ratio) as the eluent, yielding 11.2 mg of a yellow solid, namely compound 1a.

[0018] Compound 1a (11 mg, 0.013 mmol) was added to a strictly baked reaction flask, and after at least three evacuation operations involving vacuum and argon purging, it was dissolved in 10 mL of dry dichloromethane. The reaction system was then cooled to 0 °C. oAfter stabilizing at C for a short time, ferric chloride (8.3 mg, 0.05 mmol) was dissolved in nitromethane (0.5 mL) and added dropwise. o The reaction was carried out at C for 1 h. Then, 3 mL of methanol solution was added, and the solvent was removed under reduced pressure. The crude product was then separated by column chromatography using 200-300 mesh silica gel as the stationary phase and dichloromethane:petroleum ether = 1:7 (volume ratio) as the eluent, yielding an orange-yellow solid powder, which was compound 1. Yield: 6.7 mg, yield: 61%.

[0019] Molecular ion (C) determined by mass spectrometry analysis 65 H 54 B2) Mass: 856.4483 (calculated value: 856.4432). Theoretical element content (%) C 65 H 54 B2: C, 91.12; H, 6.35; B, 2.52; Measured element content (%): C, 91.18; H, 6.41.

[0020] Example 2: Synthesis of Compound 2 Tricoordinated boron unit 12 (45 mg, 0.092 mmol), cuprous iodide (3.9 mg, 0.02 mmol), and tetramethylethylenediamine (2.1 mg, 0.02 mmol) were added to a dry reaction flask. After performing at least three evacuation operations involving vacuum and argon purging, acetone was injected. Then, 25... o The reaction proceeded for 6 hours. After the reaction was complete, the reaction mixture was added to water, and the aqueous phase was extracted three times with toluene (30 mL). The resulting toluene phase was washed once with water, and the organic phases were combined and dried over anhydrous sodium sulfate. After removing toluene under reduced pressure, the crude product was separated by column chromatography using 200-300 mesh silica gel as the stationary phase and dichloromethane:petroleum ether = 1:8 (volume ratio) as the eluent, yielding 41 mg of a yellow solid, namely compound 2a.

[0021] Compound 2a (41 mg, 0.042 mmol) was added to a strictly baked reaction flask, and after at least three evacuation operations involving vacuum and argon purging, it was dissolved in 5 mL of dry dichloromethane. The reaction system was then cooled to -78°C. o After stabilizing at -78°C for a short time, iodine chloride (33.9 mg, 0.21 mmol) was dissolved in dry dichloromethane (3 mL) and added dropwise. o C gradually rises to 25 oThe reaction was carried out at C for 5 h. Then, 5 mL of sodium thiosulfate solution was added, and the aqueous phase was extracted three times with dichloromethane (30 mL). The resulting dichloromethane phase was washed once with water, and the organic phases were combined and dried over anhydrous sodium sulfate. After removing the solvent under reduced pressure, the crude product was separated by column chromatography using 200-300 mesh silica gel as the stationary phase and dichloromethane:petroleum ether = 1:6 (volume ratio) as the eluent, yielding 28 mg of an orange-red solid powder.

[0022] The resulting orange-red solid was dissolved in 9 mL of acetone and added to a light reaction flask. A small amount of elemental iodine was added, followed by 80 μl of triethylamine. 25 o The reaction was carried out at C for 3 h. The solvent was then removed under reduced pressure. The crude product was separated by column chromatography using 200-300 mesh silica gel as the stationary phase and dichloromethane:petroleum ether = 1:5 (volume ratio) as the eluent, yielding a purplish-red solid powder, which was compound 2. Yield: 12 mg, 43%.

[0023] Molecular ion (C) determined by mass spectrometry analysis 74 H 64 B2) Mass: 974.5203 ​​(calculated value: 974.5216). Theoretical element content (%) C 74 H 64 B2: C, 91.17; H, 6.62; B, 2.22; Measured element content (%): C, 91.06; H, 6.56.

[0024] Example 3: Synthesis of Compound 3 Tricoordinated boron unit 11 (55.5 mg, 0.11 mmol), 2',5'-dipinacolboryl ester-4,4''-di-tert-butyl-1,1':4',1''-terphenyl (30 mg, 0.05 mmol), tetraphenylphosphine palladium (2.3 mg, 0.002 mmol), 2-dicyclohexylphosphine-2',6'-dimethoxy-1,1'-diphenyl (1.6 mg, 0.004 mmol), and potassium phosphate (42.4 mg, 0.2 mmol) were added to a dry reaction flask equipped with a condenser. After performing vacuuming and argon purging at least three times, dry toluene (8 mL), deoxygenated ethanol (1.5 mL), and deoxygenated water (1.5 mL) were added sequentially. The temperature was then raised to 100°C. oThe reaction was carried out at C for 5 h. After the reaction was completed, the reaction mixture was added to water, and the aqueous phase was extracted three times with ethyl acetate (20 mL). The resulting ethyl acetate phase was washed once with water, and the organic phases were combined and dried over anhydrous sodium sulfate. After removing ethyl acetate under reduced pressure, the crude product was separated by column chromatography using 200-300 mesh silica gel as the stationary phase and dichloromethane:petroleum ether = 1:6 (volume ratio) as the eluent to obtain 38 mg of yellow solid, namely compound 3a.

[0025] Compound 3a (38 mg, 0.030 mmol) and 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (81.9 mg, 0.36 mmol) were added to a strictly baked reaction flask. After undergoing at least three evacuation operations with argon gas purging, the mixture was dissolved in 20 mL of dry dichloromethane. The reaction system was then cooled to 0 °C. o After stabilizing at C for a short time, ferric chloride (58.5 mg, 0.36 mmol) was dissolved in nitromethane (1 mL) and added dropwise. o C to 25 o The reaction was carried out at C for 1 h. Then, 3 mL of methanol solution was added, and the solvent was removed under reduced pressure. The crude product was then separated by column chromatography using 200-300 mesh silica gel as the stationary phase and dichloromethane:petroleum ether = 1:6 (volume ratio) as the eluent, yielding a purple solid powder, which was compound 3. Yield: 4 mg, 10%.

[0026] Molecular ion (C) determined by mass spectrometry analysis 96 H 88 B2) Mass: 1262.7056 (calculated value: 1262.7098). Theoretical element content (%) C 96 H 88 B2: C, 91.27; H, 7.02; B, 1.71; Measured element content (%): C, 91.22; H, 7.00.

[0027] Example 4: Synthesis of Compound 4 Tricoordinated boron unit 12 (50 mg, 0.10 mmol), 2',5'-diiodo-4,4''-di-tert-butyl-1,1':4',1”-terphenyl (20 mg, 0.034 mmol), palladium acetate (4.6 mg, 0.020 mmol), 2-bicyclohexylphosphine-2',4',6'-triisopropylbiphenyl (19 mg, 0.040 mmol), and potassium phosphate (64.9 mg, 0.31 mmol) were added to a dry reaction flask equipped with a condenser. After performing vacuuming and argon purging operations more than three times, dry N,N-dimethylformamide (8 mL) was injected, followed by 25... o The reaction was carried out at C for 5 h. After the reaction was completed, the reaction mixture was added to water, and the aqueous phase was extracted three times with ethyl acetate (20 mL). The resulting ethyl acetate phase was washed once with water, and the organic phases were combined and dried over anhydrous sodium sulfate. After removing ethyl acetate under reduced pressure, the crude product was separated by column chromatography using 200-300 mesh silica gel as the stationary phase and dichloromethane:petroleum ether = 1:10 (volume ratio) as the eluent to obtain 25 mg of a brownish-yellow solid, namely compound 4a.

[0028] Compound 4a (25 mg, 0.019 mmol) was dissolved in 15 mL of dry dichloromethane. The reaction mixture was then cooled to -78°C. o After stabilizing at -78°C for a short time, dissolve iodine chloride (60 mg, 0.37 mmol) in dry dichloromethane (1 ml) and add it dropwise. o C gradually rises to 25 o The reaction was carried out at C for 5 h. Then, 5 mL of sodium thiosulfate solution was added, and the aqueous phase was extracted three times with dichloromethane (30 mL). The resulting dichloromethane phase was washed once with water, and the organic phases were combined and dried over anhydrous sodium sulfate. After removing the solvent under reduced pressure, the crude product was separated by column chromatography using 200-300 mesh silica gel as the stationary phase and dichloromethane:petroleum ether = 1:7 (volume ratio) as the eluent, yielding 23.6 mg of a yellow solid.

[0029] The resulting yellow solid was placed in a strictly baked reaction flask and subjected to at least three vacuum and argon purging operations before being dissolved in 15 mL of dry dichloromethane. The reaction system was then cooled to 0 °C. o After stabilizing at C for a short time, ferric chloride (45.0 mg, 0.28 mmol) was dissolved in nitromethane (1 mL) and added dropwise. o The reaction was carried out at C for 30 min. Then, 3 mL of methanol solution was added, and the solvent was removed under reduced pressure. The crude product was then separated by column chromatography using 200-300 mesh silica gel as the stationary phase and dichloromethane:petroleum ether = 1:1 (volume ratio) as the eluent, yielding a brownish-yellow powder, which was compound 4. The yield was 15.3 mg, or 65%.

[0030] Molecular ion (C) determined by mass spectrometry analysis 100 H 84 B2) Mass: 1306.6708 (calculated value: 1306.6785). Theoretical element content (%) C 100 H 84 B2: C, 91.87; H, 6.48; B, 1.65; Measured element content (%): C, 91.82; H, 6.45.

[0031] Example 5: Synthesis of Compound 5 Tricoordinated boron unit 12 (67 mg, 0.137 mmol), 2-bromo-1,4-diiodobenzene (20 mg, 0.049 mmol), bis(triphenylphosphine)palladium dichloride (3.4 mg, 0.0048 mmol), and cuprous iodide (1.9 mg, 0.001 mmol) were added to a dry reaction flask equipped with a condenser. After performing vacuuming and argon purging operations more than three times, dry triethylamine (2 mL) and dry tetrahydrofuran (10 mL) were injected, followed by 25... o The reaction was carried out at C for 5 h. After the reaction was completed, the reaction mixture was added to water, and the aqueous phase was extracted three times with ethyl acetate (20 mL). The resulting ethyl acetate phase was washed once with water, and the organic phases were combined and dried over anhydrous sodium sulfate. After removing ethyl acetate under reduced pressure, the crude product was separated by column chromatography using 200-300 mesh silica gel as the stationary phase and dichloromethane:petroleum ether = 1:7 (volume ratio) as the eluent to obtain 39.5 mg of a yellow solid.

[0032] A yellow solid (39.5 mg, 0.035 mmol) and platinum dichloride (9.3 mg, 0.035 mmol) were added to a dry reaction flask equipped with a condenser. After performing vacuuming and argon purging at least three times, 10 mL of dry o-dichlorobenzene was injected. The reaction system was heated to 150 °C. o The reaction was carried out at C for 24 h. After the reaction was completed, the reaction mixture was added to water, and the aqueous phase was extracted three times with ethyl acetate (20 mL). The resulting ethyl acetate phase was washed once with water, and the organic phases were combined and dried over anhydrous sodium sulfate. After removing the solvent under reduced pressure, the crude product was separated by column chromatography using 200-300 mesh silica gel as the stationary phase and dichloromethane:petroleum ether = 1:5 (volume ratio) as the eluent, yielding 24.8 mg of an orange-yellow solid powder.

[0033] The resulting orange-yellow solid was placed in a strictly baked reaction flask, and after three or more vacuum and argon gas purging operations, it was dissolved in 10 mL of dry dichloromethane. The reaction system was then cooled to 0 °C. o After stabilizing at C for a short time, ferric chloride (53.2 mg, 0.33 mmol) was dissolved in nitromethane (1 mL) and added dropwise. o The reaction was carried out at C for 1 h. Subsequently, 3 mL of methanol solution was added, and the solvent was removed under reduced pressure. The crude product was separated by column chromatography using 200-300 mesh silica gel as the stationary phase and dichloromethane:petroleum ether = 1:5 (volume ratio) as the eluent to obtain 10.4 mg of dark red solid powder, which is compound 5a.

[0034] Compound 5a (10.4 mg, 0.01 mmol) was added to a strictly baked reaction flask, and after at least three evacuation operations involving vacuum and argon purging, it was dissolved in 30 mL of dry tetrahydrofuran. The reaction system was then cooled to 0 °C. o After stabilizing at C for a short time, n-butyllithium (0.008 mL, 0.0133 mmol) was added dropwise. o C gradually rises to 25 o The reaction was carried out at C for 3 h. Then, 1 mL of water was added, and the solvent was removed under reduced pressure. The crude product was then separated by column chromatography using 200-300 mesh silica gel as the stationary phase and dichloromethane:petroleum ether = 1:5 (volume ratio) as the eluent to obtain compound 5. The yield was 8.8 mg, or 85%.

[0035] Molecular ion (C) determined by mass spectrometry analysis 80 H 66 B2) Mass: 1048.5389 (calculated value: 1048.5351). Theoretical element content (%) C 80 H 66 B2: C, 91.60; H, 6.34; B, 2.06; Measured element content (%): C, 91.82; H, 6.56.

[0036] Example 6: Synthesis of Compound 6 Compound 5a (58.3 mg, 0.052 mmol), 2,2'-biphenyl diboronic acid (5 mg, 0.021 mmol), tetrakis(triphenylphosphine) palladium (4.8 mg, 0.004 mmol), 2-dicyclohexylphosphine-2',6'-dimethoxy-1,1'-dibiphenyl (3.4 mg, 0.08 mmol), and potassium phosphate (2.2 mg, 0.013 mmol) were added to a dry reaction flask equipped with a condenser. After three or more evacuation operations involving vacuuming and purging with argon, dry toluene (8 mL), deoxygenated ethanol (1 mL), and deoxygenated water (1 mL) were sequentially added. The temperature was then raised to 100°C. o The reaction was carried out at C for 5 h. After the reaction was completed, the reaction mixture was added to water, and the aqueous phase was extracted three times with ethyl acetate (30 mL). The resulting ethyl acetate phase was washed once with water, and the organic phases were combined and dried over anhydrous sodium sulfate. After removing ethyl acetate under reduced pressure, the crude product was separated by column chromatography using 200-300 mesh silica gel as the stationary phase and dichloromethane:petroleum ether = 1:5 (volume ratio) as the eluent, yielding 37.6 mg of an orange-red solid, which was compound 6a.

[0037] Compound 6a (25 mg, 0.011 mmol) was added to a strictly baked reaction flask, and after at least three evacuation operations involving vacuum and argon purging, it was dissolved in 15 mL of dry dichloromethane. The reaction system was then cooled to 0 °C. o After stabilizing at C for a short time, ferric chloride (108.2 mg, 0.667 mmol) was dissolved in nitromethane (3 mL) and added dropwise. o The temperature was gradually increased to room temperature and the reaction proceeded for 1 hour. Then, 3 mL of methanol solution was added, and the solvent was removed under reduced pressure. The crude product was then separated by column chromatography using 200-300 mesh silica gel as the stationary phase and dichloromethane:petroleum ether = 1:3 (volume ratio) as the eluent to obtain a purplish-black solid powder, namely compound 6. The yield was 11.2 mg, or 45%.

[0038] Molecular ion (C) determined by mass spectrometry analysis 172 H 126 B4) Mass: 2236.0284 (calculated value: 2236.0265). Theoretical element content (%) C 172 H 126 B4: C, 92.39; H, 5.68; B, 1.93; Measured element content (%): C, 92.45; H, 5.71.

[0039] Example 7: Synthesis of Compound 7 Following the reaction conditions and process of Example 4, using tricoordinated boron unit 12 and 5,12-bis(4-(tert-butyl)phenyl)-1,8-diiodobenzo[k]tetraphenyl as raw materials, a purple solid, namely compound 7a, was obtained. Subsequently, a black solid powder, namely compound 7, was obtained.

[0040] Molecular ion (C) determined by mass spectrometry analysis 116 H 92 B2) Mass: 1507.7456 (calculated value: 1507.7419). Theoretical element content (%) C 116 H 92 B2: C, 92.41; H, 6.15; B, 1.43; Measured element content (%): C, 92.48; H, 6.12.

[0041] Example 8: Synthesis of Compound 8 Following the reaction conditions and process of Example 1, compound 8a was prepared using tricoordinated boron unit 11 and 10-pinacolboryl ester-1,8-bis(trimethylphenoxy)anthracene as raw materials. A purplish-black solid powder, namely compound 8, was then obtained.

[0042] Molecular ion (C) determined by mass spectrometry analysis 67 H 57 The mass of BO2 is 904.4489 (calculated value: 904.4452). Theoretical elemental content (%) C 67 H 57 BO2: C, 88.92; H, 6.35; B, 1.19; O, 3.54; Measured element content (%): C, 88.98; H, 6.33.

[0043] Example 9: Synthesis of Compound 9 Following the reaction conditions and process of Example 1, using tricoordinated boron unit 11 and naphthalene dibromodiborate as raw materials, a purplish-black solid powder 9a was obtained.

[0044] Compound 9a (60 mg, 0.050 mmol) was added to a strictly baked reaction flask and subjected to at least three evacuation operations involving vacuum and argon purging. The solution was then dissolved in 30 mL of dry tetrahydrofuran. The reaction system was cooled to 0 °C. o After step C, n-butyllithium (0.060 mL, 0.10 mmol) was added dropwise. o C gradually rises to 25 oThe reaction was carried out at C for 3 h. Then, 1 mL of water was added, and the solvent was removed under reduced pressure. The crude product was then separated by column chromatography using 200-300 mesh silica gel as the stationary phase and dichloromethane:petroleum ether = 1:3 (volume ratio) as the eluent to obtain a black solid powder, namely compound 9. The yield was 31.4 mg, or 60%.

[0045] Molecular ion (C) determined by mass spectrometry analysis 80 H 64 B2) Mass: 1048.5387 (calculated value: 1048.5351). Theoretical element content (%) C 80 H 66 B2: C, 91.60; H, 6.34; B, 2.06; Measured element content (%): C, 91.67; H, 6.36.

[0046] Example 10: Synthesis of Compound 10 Following the reaction conditions and process of Example 1, using compound 9a and p-tert-butylphenylboronic acid as raw materials, a purplish-black powder, namely compound 10, was finally obtained.

[0047] Molecular ion (C) determined by mass spectrometry analysis 100 H 82 B2) Mass: 1305.6680 (calculated value: 1305.6636). Theoretical element content (%) C 100 H 82 B2: C, 92.01; H, 6.33; B, 1.66; Measured element content (%): C, 92.06; H, 6.35.

[0048] Given that graphene nanoparticles are prone to aggregation, making it difficult to obtain clear 1H NMR spectra, high-resolution mass spectrometry, full-spectrum mass spectrometry, and elemental analysis were used to confirm the molecular structure. Some results are shown below. Figure 1 As shown. The boron-impregnated graphene nanomaterials synthesized in Examples 1-4 were subjected to UV-Vis absorption spectroscopy analysis, and the results are as follows. Figure 2 As shown, the main absorption peak of compound 1 is at 492 nm; the main absorption peaks of compound 2 are at 561 nm and 521 nm; the main absorption peaks of compound 3 are at 592 nm and 503 nm; and the main absorption peaks of compound 4 are at 599 nm and 549 nm, exhibiting light absorption properties from the visible to the near-infrared region. Emission spectroscopy analysis was performed on the boron-impregnated graphene nanomaterials synthesized in Examples 1-4, and the results are as follows: Figure 3As shown, compound 1 has an emission peak at 520 nm; compound 2 has an emission peak at 576 nm; compound 3 has an emission peak at 618 nm; and compound 4 has an emission peak at 621 nm, exhibiting fluorescence properties with effectively tunable emission color. Figure 4-6 As shown, the spontaneous emission properties of the boron-impregnated graphene nanomaterials synthesized in Examples 1-3 were studied in an amplified manner. The ASE peak of compound 1 was located at 558 nm, and the threshold was 160 kW cm⁻¹. -2 The ASE peak of compound 2 is located at 621 nm, with a threshold of 230 kW cm⁻¹. -2 The ASE peak of compound 3 is located at 674 nm, with a threshold of 120 kW cm⁻¹. -2 .

[0049] The boron-containing graphene nanoparticles of the present invention exhibit amplified spontaneous emission properties, and these compounds can be purified by column chromatography using silica gel columns, indicating that they possess good stability and have potential application as laser gain medium materials.

[0050] Obviously, the above embodiments are merely examples for clear illustration and are not intended to limit the embodiments. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all embodiments here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A boron-impregnated graphene nanomaterial, characterized in that, The structural formula is one of the following: 。 2. The application of the boron-hybridized graphene nanoluminescent material according to claim 1 as an organic laser gain medium material.